2008
DOI: 10.1016/j.vaccine.2008.03.092
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the HIV-1 env gp160 gene to improve pDNA vaccine-elicited cell-mediated immune responses

Abstract: Plasmid DNA (pDNA) vaccines are effective at eliciting immune responses in a wide variety of animal model systems, however, pDNA vaccines have generally been incapable of inducing robust immune responses in clinical trials. Therefore, to identify means to improve pDNA vaccine performance, we compared various post-transcriptional and post-translational genetic modifications for their ability to improve antigen-specific CMI responses. Mice vaccinated using a sub-optimal 100 mcg dose of a pDNA encoding an unmodif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 85 publications
(98 reference statements)
2
14
0
Order By: Relevance
“…It is likely that the structure and intracellular trafficking of these hybrid Env proteins is altered by the N-terminal modifications, affecting the processing of the precursor gp160. The HIV-1 env 6101 (clade B) expression plasmids producing the native and modified forms were previously described [44]. Similarly, we found that upon fusion of the tPA signal peptide to HIVenv 6101 less gp120 was produced and that the MCP-3 env fusion showed very poor gp120 production (data not shown), in agreement with the SIV Env results (see above).…”
Section: Resultssupporting
confidence: 88%
“…It is likely that the structure and intracellular trafficking of these hybrid Env proteins is altered by the N-terminal modifications, affecting the processing of the precursor gp160. The HIV-1 env 6101 (clade B) expression plasmids producing the native and modified forms were previously described [44]. Similarly, we found that upon fusion of the tPA signal peptide to HIVenv 6101 less gp120 was produced and that the MCP-3 env fusion showed very poor gp120 production (data not shown), in agreement with the SIV Env results (see above).…”
Section: Resultssupporting
confidence: 88%
“…Codon optimization has previously been successfully used to boost the expression of several other retroviral proteins, including envelope glycoproteins (18,45). Full-length retroviral genomes require a balanced expression of their proteins for optimal replication, and their DNA, RNA, and protein sequences are under a multitude of constraints and selective pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The pathway for these immunogens begins with the design of the mosaic protein sequences, followed by the design of a "humanized" gene to optimize their expression (65), the synthesis and expression of the genes, and then the study of the properties of the proteins, including binding to relevant antibodies. After this is accomplished, the immunogenicity of the constructs is assessed with mice.…”
Section: Polyvalent Mosaic Vaccinesmentioning
confidence: 99%